2017
DOI: 10.21162/pakjas/17.6324
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Potential of Upland Cotton for Water Stress Tolerance

Abstract: To develop genotypes that can yield, better under water stress conditions, plant breeders must have knowledge about gene action and combining abilities of parents for various quantitative traits related to drought tolerance. The objective of the study was to provoke genetic information which may be used in cotton breeding program to enhance drought tolerance. Thirty cotton genotypes were screened on the basis of root and shoot length at seedling stage in glasshouse. Ten cotton genotypes namely NIAB-111, CP-15/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Furthermore, σ 2 A was not significant in many cases indicating the importance of dominance or non-additive in the inheritance of these traits in these materials. Rehman et al (2017) noted predominance of non-additive genetic effects in the inheritance of the characters studied. Kannan & Saravanan (2016) found that ratio of variance due to GCA to that of SCA was less than one for all the character under study indicating importance of dominance gene effects in the inheritance of all characters.…”
Section: The Role Of Additive and Non-additive Gene Effects In The In...mentioning
confidence: 91%
“…Furthermore, σ 2 A was not significant in many cases indicating the importance of dominance or non-additive in the inheritance of these traits in these materials. Rehman et al (2017) noted predominance of non-additive genetic effects in the inheritance of the characters studied. Kannan & Saravanan (2016) found that ratio of variance due to GCA to that of SCA was less than one for all the character under study indicating importance of dominance gene effects in the inheritance of all characters.…”
Section: The Role Of Additive and Non-additive Gene Effects In The In...mentioning
confidence: 91%
“…Water stress decreases the leaf area of cotton. For instance, Rehman et al [85] studied parents and F1 hybrids grown under three different irrigation regimes (none, deficit, and normal irrigation) and observed a reduction in leaf area under water-limited conditions. Moreover, cotton grown under drought has a lower relative water content (RWC).…”
Section: Response Of Cotton Physiological Traits Yield and Yield Components To Irrigation Regimesmentioning
confidence: 99%